2022
DOI: 10.3390/ijerph191912376
|View full text |Cite
|
Sign up to set email alerts
|

Association of Personality Traits with Life and Work of Medical Students: An Integrative Review

Abstract: Background: Personality traits are the basic components of an individual’s personality. Although there are many published articles about the impact of personality traits on medical students, there is a lack of integrative reviews of existing articles. To close this gap, this review aims to summarize the impact of personality traits on medical students from two perspectives: life and work. Methods: The search was performed using the following databases: PubMed, Web of Science, Google Scholar, and EMBASE. All pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…In the assessment of medical skills (columns (4) to (6) in Table 4), participants' gender does not play a role, and the influence of nationality and school background is less pronounced than in the overall OSCE result. Only students from the special quotas differ significantly from their peers in columns ( 4) and (5). Controlling for age and Abitur (model ( 6)) resolves this difference, and the estimate for waiting list students' score is now 6 percentage points above their NC-quota classmates.…”
Section: Columns (1)-(3) Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…In the assessment of medical skills (columns (4) to (6) in Table 4), participants' gender does not play a role, and the influence of nationality and school background is less pronounced than in the overall OSCE result. Only students from the special quotas differ significantly from their peers in columns ( 4) and (5). Controlling for age and Abitur (model ( 6)) resolves this difference, and the estimate for waiting list students' score is now 6 percentage points above their NC-quota classmates.…”
Section: Columns (1)-(3) Ofmentioning
confidence: 93%
“…Even if they are under-represented in exams, traits targeted with non-cognitive selection criteria (practical experiences, empathy, responsibility, confidence in patient-doctor communications and interactions) are undoubtedly crucial soft-skills required in the medical profession [4,5]. In recent years, several educational policy reforms in Germany have sought to strengthen the role of practical and social skills in medical curricula, which resulted inter alia in the passage of a national competency-based learning objective catalogue ('Nationaler Kompetenzbasierter Lernzielkatalog' (NKLM) [6,7]) and in drafts for an updated medical licensure act.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of personality traits has been extensively studied by psychologists, with different models proposed over the years [52][53][54]. Research has shown that personality traits can influence numerous facets of an individual's life, including academic and work performance, relationships, and health [55]. Understanding the relationship between personality traits and different outcomes can help individuals and organizations make better decisions [56].…”
Section: Personality Traitsmentioning
confidence: 99%
“…Physicians' personality characteristics have been focused mainly on medical education [9,10]; in particular, the Big Five personality traits (also known as the five-factor model of personality) consisting of extraversion, agreeableness, openness, conscientiousness, and emotional stability have been examined. [11][12][13] A study examining physician personality characteristics associated with physician satisfaction ratings showed that a high level of openness, linked to imagination and intellectual curiosity, [13] was associated with greater patient satisfaction, suggesting the importance of an empathetic response and an atmosphere that easily allows for discussion. [14] Moreover, an average level, rather than overly high levels, of physician conscientiousness was associated with higher physician ratings.…”
Section: Introductionmentioning
confidence: 99%